A three phase hybrid approach for enhancement of coverage in wireless sensor network - Biradar, Shobha; Shastry P. M, Mallikarjuna (International Journal of Engineering and Technology, 2018)
In Wireless Sensor Network, when sensor nodes are deployed using random deployment method, the given area of interest may not be covered completely and coverage holes may also exist. But, coverage of region of interest can be enhanced by moving sensors to optimal positions. In this paper, a three phase hybrid approach for enhancement of coverage is proposed and implemented. In first phase, sensor nodes are deployed at random positions in the given region of interest. In second phase, a heuristic function is used to determine the optimal positions based on the Euclidian distance between any two optimal positions. In third phase, only the nodes which are close to the optimal positions are chosen and moved. But, rest of the nodes are not moved. They remain at same position, where they were deployed in first stage. Since, some are static and some are moved, this approach is termed as Hybrid approach. Simulation results are presented with      different number of sensor nodes and different size of region of interest. The proposed new algorithm performs better in terms of coverage of region of interest, number of movements, average distance moved and number of rounds required to converge than the other coverage enhancement algorithms.